Use of ICT by the University Students Exploring difference between Book, Noticeboard and ICT for knowledge and Information Seeking - Anis, Fahad; Siraj, Syed Abdul (Journal of Peace, Development and Communication, 2020)
The study investigates Universities’ students use of Information and Communication Technology (ICT) for leaning and a comparison between book and ICT in obtaining knowledge. The study highlights public and private universities students banking on ICT for seeking knowledge and information. Besides, the study focuses on the facilitation and acquiring gratification from ICT in terms of entertainment, socialization, and scholastic achievement. The results show that student seek greater knowledge from ICT than the book. Similarly, they get quick information from ICT than the noticeboard. The use of ICT also gratifies them for entertainment, socialization, and scholastic achievement. Moreover, the study does not find significant difference among the students of public and private universities for seeking knowledge from ICT. Key Words: Use of ICT, Differences of Book, Noticeboard and ICT, ICT and Gratification.